The Synthesis And Characterization Of Anodic Alumina Oxide Using Sulfuric Acid And Oxalic Acid - Nur Afieqah Md. Ghazazi; Muhammad Zamir Othman; Syahida Suhaimi (Trans Tech Publications Ltd, 2024)
Indexed by WOS